2008
DOI: 10.1001/archsurg.2007.77
|View full text |Cite
|
Sign up to set email alerts
|

Association of Morbid Obesity With FTO and INSIG2 Allelic Variants

Abstract: Increased BMI in morbid obesity is associated with a combination of FTO and INSIG2 SNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 36 publications
1
41
2
2
Order By: Relevance
“…1 a) [Dina et al, 2007;Chu et al, 2008]. In our patients, the AA genotype was even more frequent (32.3 vs. 21%) and the TT genotype less frequent (19.4 vs. 31%) than in the Pennsylvanian cohort of 707 morbidly obese subjects, whereas the AT genotype was observed at a similar frequency (48%) [Chu et al, 2008].…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…1 a) [Dina et al, 2007;Chu et al, 2008]. In our patients, the AA genotype was even more frequent (32.3 vs. 21%) and the TT genotype less frequent (19.4 vs. 31%) than in the Pennsylvanian cohort of 707 morbidly obese subjects, whereas the AT genotype was observed at a similar frequency (48%) [Chu et al, 2008].…”
Section: Discussioncontrasting
confidence: 41%
“…However, even this association was not supported by our findings. Chu et al [2008] found the strongest association with BMI, when both genes were affected and proposed interactions between FTO and INSIG2 . In another study, the INSIG2 CC genotype was found negatively associated with weight loss in a lifestyle intervention program in overweight children and adolescents.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…FTO/INSIG2 double homozygotes and homozygote/heterozygote pairs had significantly higher BMI than other genotypes. Independent analyses of each gene do not show relationship with BMI [40].…”
Section: Discussionmentioning
confidence: 82%
“…All patients who were enrolled in the Bariatric Surgery Program of the Geisinger Center for Nutrition and Weight Management between October 2004 and October 2010 were offered the opportunity to participate in the study (41). Over 90% of patients consented to participate.…”
Section: Methodsmentioning
confidence: 99%